Honey flipper collector / Mohamad Tarmizie Kamaludin...[et al.] - Kamaludin, Mohamad Tarmizie; Hamka, Nazlyatul Najwa; Mohd Johari, Nisa Aqidah; Abang Zainoren, Dayang Athirah; Khalik, Adif Aliff (2019)
People who owned stingless beehive has always been quite a task of getting the honey to be extracted. Our Honey Flip Collector will provide much simply way to get stingless bee honey flow right out of the hive. Our company designed Honey Flip Collector is mainly for stingless beehive only. This product is for people who have pain in getting the honey which need to make fire up a smoker to sedate bees, pull out the frames and trying not to squash the bees, poke the wax capping, filter the honey, clean up all the mess and the frames have to go back to the hives again. Honey Flip Collector will be a huge help to extract honey easily by turn a tap, sit back and watch the honey pour out. This product will be develop based on the information that has been collected through online survey and questionnaire. The results positively indicate that consumers are really demanding for many stingless beehive owners since it required a lot of process to be outcome. In the findings, there are problems which has been analysed. Honey harvesting is a process of harvesting the honey which are commonly time consuming that makes the production of honey becomes low and in order to gain high production of honey, it would take a longer time to do so. Regarding this issue, the honeybee entrepreneur can enhance the process of honey harvesting by implementing a honey flip collector for this honey harvesting process. Usually the machine sold in the market for honey harvesting are more expensive, but the function is quite same with the traditional way. This may be the reason the honeybee entrepreneur becomes less interested in the machine and decided to use the traditional way instead. Honey flip collector is created especially for stingless honeybee. It is the most convenient way to harvest the honey which is less time consuming and convenient to use. Giving the best way to harvest the honey at the same time can produce a lot of honey in a shorter time compared to traditional way.